Addressing diagnostic challenges in primary immunodeficiencies: Laboratory evaluation of Toll-like receptor- and NF-κB-mediated immune responses. (April 2014) - Frans, Glynis; Meyts, Isabelle; Picard, Capucine; Puel, Anne; Zhang, Shen-Ying; Moens, Leen; Wuyts, Greet; Van der Werff Ten Bosch, Jutte; Casanova, Jean-Laurent; Bossuyt, Xavier
Abstract Toll-like receptors (TLRs) play an important role in immunity and mediate their actions via multiple signaling pathways, in particular, the nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-κB) pathway. Rare inherited defects of TLR- and NF-κB-dependent responses have recently been recognized. These primary immunodeficiencies predispose children to life-threatening infections and often remain undiagnosed. Establishing a sensitive, specific, cost-effective and simple method for diagnosis is therefore important. In this article, we review the known defects of TLR- and NF-κB-mediated pathways and the assays that can be used to screen for such defects.